Technology Absorption as a Main Indicator of Global Entrepreneurship Performance - Prasetyo, P Eko (Universitas Negeri Semarang, 2020)
In the globalization era, technology absorption capacity is increasingly vital to own to improve the performance of entrepreneurial industry. The aim of this study was to elaborate the main role of technology absorption as the main determinant to boost the performance of global entrepreneurship. For the sake of analysis, the researchers took primary data from global entrepreneurship index (GEIINDEX, 2019) containing 137 countries that have been surveyed (Acs, 2019). The method of analysis used was path analysis model in recursive form derived from the experimental model of multiple regression method in form of ordinary least square (OLS). The results showed that technology absorption (TA) positively and significantly became the main determinant in improving the capacity and performance of global entrepreneurship, while the opportunity start-up (OS) was the supporting determinant. Shortly, the entrepreneurial industry should have the capacity of technology absorption and mastery to start a business (OS), improve capacity (ABT), and sustainably encourage the excellence of Global Entrepreneurship Performance (GEP)